(untitled) (Nóema, 2013)
The human experiences and acts are ruled by the power of culture. This power concerns the invisible and unperceived action of innumerable machines or apparatus: the extra-somatic tools born during the human evolution. The paper develops this subject in order to explain the pedagogical consequences of the practical action of thought.